Sleep symptoms and polysomnographic architecture in advanced Parkinson's disease after chronic bilateral subthalamic stimulation. Issue 5 (1st May 2002) - Iranzo, A; Valldeoriola, F; Santamaría, J; Tolosa, E; Rumià, J
Abstract : Objective: To evaluate the sleep symptoms and polysomnographic architecture in advanced Parkinson's disease after chronic bilateral subthalamic stimulation (STN-DBS). Methods: Sleep was studied in 11 patients (six women and five men; mean (SD) age 63.6 (7.8) years) who underwent STN-DBS. Subjective sleep evaluation was assessed by clinical sleep interview and the Pittsburgh sleep quality index (PSQI) questionnaire, and sleep architecture by polysomnography with audiovisual recording. Nocturnal mobility was evaluated. Results: Before surgery, eight patients rated their sleep quality as unsatisfactory; seven of these had a marked improvement after surgery, and the PSQI questionnaire showed significantly improved sleep quality. After surgery, polysomnography showed an increase in the longest period of uninterrupted sleep and a decrease in the arousal index. There was an increase in nocturnal mobility after surgery, but no change in REM sleep behaviour disorder. Conclusions: In advanced Parkinson's disease, chronic STN-DBS is associated with subjective improvement in sleep quality, probably through increased nocturnal mobility and reduction of sleep fragmentation.